(untitled) (Nepal Medical College Journal, 2021)
Over the past few decades, alcohol consumption has increased in quantity and frequency. Several studies have suggested that people who start drinking at younger age have an increased risk of alcohol use disorder. This study was carried out to assess the pattern of alcohol consumption in relation to the age of initiation of alcohol use among the residents of Jhaukhel area of Bhaktapur district. A cross sectional descriptive survey was conducted in Jhaukhel area of Bhaktapur district among the permanent residents aged 15 years and above through a purposive sampling technique using a pre tested self-constructed proforma. Assessment of alcohol use, harmful/ hazardous drinking and alcohol dependence was done using an AUDIT questionnaire as a tool. Chi-square test and Fisher’s exact test were applied and ‘p’ value was calculated to see the association between age of onset of alcohol use and the alcohol use pattern and effects. The level of significance was set at 5%, and ‘p’ value of < 0.05 was considered statistically significant. A total of 190 respondents were interviewed. Mean age of the respondents was 41.25 ± 16.4 years while mean age of initiation of alcohol consumption was 20 ± 4.3 years and 31 (30.4 %) of drinkers initiated alcohol consumption before legal drinking age (18 years). This was more among males (36.5%) than females (14.3%), (p-value: 0.03, OR: 3.4, 95%CI: 1-11) Initiating alcohol consumption early in life before 18 years was strongly associated with binge drinking pattern (P value: <0.001, OR: 9.5, 95%CI: 2.7-33.3). Those who initiate drinking before 18 years were more likely to suffer from alcohol related medical problems compared to those who initiated drinking after 18 years (OR: 6.63, 95% CI: 2.3-19.3, P value: 0.001). Parental consumption of alcohol was found to be associated with the early initiation of alcohol use (OR: 2.7, 95%CI: 1.01-6.96, P value: 0.03). Early initiation of alcohol consumption before legal drinking age was not only a predictor for binge drinking and alcohol dependence, but also a risk factor for alcohol related medical problem, accidents and self-inflicted injuries. Hence this is a serious issue which needs to be addressed at the individual, family as well as community level.